Assessment of Patellar Morphology in Trochlear Dysplasia on Computed Tomography Scans. Issue 2 (24th January 2021) - Li, Ming; Ji, Gang; Fan, Liu; Fan, Chong‐yi; Lin, Wei; Yang, Guang‐min; Dong, Cong‐lei; Fei, Wang
Abstract : Objective: To evaluate the patellar morphology of trochlear dysplasia and normal knees in different genders and in different severities of trochlear dysplasia on CT scans. Methods: A total of 75 patients with trochlear dysplasia (110 knees) treated at the Third Hospital of Hebei Medical University from December 2013 to December 2018 were included in an experimental group, and an age‐matched and sex‐matched cohort of 46 patients with normal trochlear shape (61 knees) were randomly selected into a control group. The experimental group was divided into a female experimental group (Group FE, 47 patients, 72 knees) and a male experimental group (Group ME, 28 patients, 38 knees); the control group was divided into a female control group (Group FC, 31 knees, 24 female patients) and a male control group (Group MC, 30 knees, 22 male patients). Furthermore, according to the severity of trochlear dysplasia, Group FE was divided into a female low‐grade dysplasia group (Group FL, 20 knees) and a female high‐grade dysplasia group (Group FH, 52 knees); Group ME was divided into a male low‐grade dysplasia group (Group ML, 16 knees) and a male high‐grade dysplasia group (Group MH, 22 knees). All participants had undergone CT scans in the supine position; the patellar width and thickness, the lateral patellar facet angle, the Wiberg angle, and the Wiberg index were measured and compared. Results: In trochlear dysplasia knees, the mean patellar width and thickness and the lateral patellar facet angle were significantly smaller; the mean Wiberg index was significantly larger than in normal knees, regardless of gender ( P < 0.05); and there was no statistically significant difference in the mean Wiberg angle ( P > 0.05). In the female groups, the mean patellar width and thickness and the Wiberg angle were significantly smaller; the mean lateral patellar facet angle was significantly larger than those in the male groups ( P < 0.05); and there was no significant difference in the mean Wiberg index ( P > 0.05). In the low‐grade dysplasia group, the mean Wiberg index was smaller than that in the high‐grade dysplasia group ( P < 0.05), regardless of gender; however, there was no significant difference in the mean patellar width and thickness, the lateral patellar facet angle, and the Wiberg angle in low‐grade and high‐grade dysplasia ( P > 0.05). Conclusion: On CT scans, the patella in trochlear dysplasia had a smaller width, a thinner thickness, a lengthened lateral facet, and a more flattened articular facet. In addition, the patellar articular facet was more prominent in female patients. With the severity of trochlear dysplasia increased, the lateral patellar facet became longer. In addition, the abnormal stress distribution on the patella influenced the patellar morphology in trochlear dysaplasia. Abstract : The author found the patella in trochlear dysplasia have a smaller width, a thinner thickness, a lengthened lateral facet, and a more flattened articular facet. In addition, the patellar articular facet was more prominent in female patients. With the severity of trochlear dysplasia increased, the lateral patellar facet became longer.